Birth Stories of Trinidad and Tobago: Dominic Charles - (:unkn) unknown (The University of the West Indies, 2024)
Dominic Charles a thirty-three year old father from Fanny Village, Point Fortin. He is the father of two children born at the San Fernando General Hospital. He shares his perpsectives as a father on birthing.
Keywords: Childbirth -- Trinidad and Tobago